A Reformulation of business education curriculum for the development of career opportunities among undergraduates of South Nigerian Universities - Ile, Chika Madu; Edokpolor, James Edomwonyi (Asian Journal of Assessment in Teaching and Learning, 2020)
Concerning on the rates social burden among the graduates of business education in Nigeria has provided an opportunity for the authors to extant the study to examine the current state of business education curriculum and the reformulation of business education curriculum equips the undergraduates with skills to start a business and engaging towards lifelong learning. A cross-sectional survey design was applied to achieve the objectives of the study. The design of the research is a quantitative method. Structured questionnaires were given to a sample of 289 participants (43 lecturers and 246 students) which were randomly selected across three universities in Nigeria. The data obtained are analyzed by the Statistical Package for Social Sciences (SPSS) version 23.0 and the mean statistic is used to answer the research questions and standard deviations are used to assess the degree to which participants’ scores are clustered around the mean. The results show that the business education curriculum is theoretical in nature, as such does not have the capability of preparing students to become entrepreneurs and lifelong learners. Hence, the data shows that most of the respondents vote for business education curriculum prepares student to work for the entrepreneurs with mean 3.49 for lecturers and 3.67 for students. Moreover, the result shows that a change in business education curriculum could help to equip students with skills to engage in becoming an entrepreneur. Therefore, the managers of business education should endeavor collaborations with major stakeholders to capable of integrating the 21st-century skills and apprenticeship models into the business education curriculum. It will help to equip undergraduates with the skills needed to pursue entrepreneurial and lifelong learning careers upon graduation.